2017
DOI: 10.1515/ract-2016-2691
|View full text |Cite
|
Sign up to set email alerts
|

Complexing power of hydro-soluble degradation products from γirradiated polyvinylchloride: influence on Eu(OH)3(s) solubility and Eu(III) speciation in neutral to alkaline environment

Abstract: AbstractThe complexing power of hydrosoluble degradation products (HDPs) from an alkaline hydrolysis of a 10 MGy γ-irradiated polyvinylchloride is studied. The complexation of Eu(III), as an analogue of lanthanide and actinide radionuclides at their +III oxidation state for oxygen containing functions, is evidenced both from the increasing of Eu(OH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 45 publications
(72 reference statements)
3
13
0
Order By: Relevance
“…supposedly mixed Eu(OH)nAdip (3-2-n)+ . But it must not be forgotten that in a previous work it has been shown that oxalate and glutarate -which are supposed to have greater complexation constants than adipate [13] -did not increase Eu(OH)3(s) solubility at pH 13.3 [38]. Even phthalic acid has not been shown to impact solubility of Eu(OH)3(s) [13].…”
Section: Theoretical Europium(iii) Speciation In Adipate Mediummentioning
confidence: 88%
See 2 more Smart Citations
“…supposedly mixed Eu(OH)nAdip (3-2-n)+ . But it must not be forgotten that in a previous work it has been shown that oxalate and glutarate -which are supposed to have greater complexation constants than adipate [13] -did not increase Eu(OH)3(s) solubility at pH 13.3 [38]. Even phthalic acid has not been shown to impact solubility of Eu(OH)3(s) [13].…”
Section: Theoretical Europium(iii) Speciation In Adipate Mediummentioning
confidence: 88%
“…The TRLS experimental set-up is slightly modified compared to the one already described elsewhere [19,[21][22][23][36][37][38]. It is including a 355 nm tripled neodymium-doped yttrium aluminium garnet (Nd:YAG) laser (Surelite, Continuum) providing ca.…”
Section: Trls Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of interactions between radionuclides and organics contaminants from radio-oxidized polymers -generated during exploitation, maintenance, and dismantling of nuclear fuel cycle facilities [1] -is crucial for assessing the mobility of radionuclides near nuclear waste geological disposals [2][3][4][5][6]. Contaminated polymers should be disposed in primary cemented packages and in cemented over-packages in intermediate level long-lived waste (ILW-LL).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting products are called hydro-soluble degradation products (HDPs). There is evidence that irradiated polymers induces bacterial nitrate reduction [9], and that HDPs are complexing radionuclides [3][4][5][6][10][11][12][13]. Most of the latter studies were focused on complexation by isosaccharinic acid -a glucose isomer and HDP from non-irradiated cellulose [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%